Fetomaternal outcome in pregnancies complicated by fibroid - Singh, Leimapokpam Roshan; Mahajan, Kaushik; Singh, Nandeibam Balchand; Singh, Wairokpam Prabinkumar; Athokpam, Kabita; Jinaluxmi, R. K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Fibromyoma (leiomyoma) is the most common benign tumour of the uterus. Approximately 10% to 30% of women with uterine fibroids developed complications during pregnancy. The aim of the study was planned to ascertain the fetomaternal outcome in pregnancies complicated by fibroid. Methods: A hospital based cross-sectional study was conducted among pregnant women with documented uterine fibroid who was admitted for any complication or delivered in the department of obstetrics and gynaecology, RIMS, Imphal from September 2017 to August, 2019 in the department of obstetrics and gynaecology in collaboration with department of paediatrics, Regional institute of Medical Sciences, Imphal. Detailed clinical history and socio-demographic profile were recorded in pre-designed proforma. General physical examination and systemic examination and obstetrical examination was carried out for the participants. Results: Major proportions was in the age group of 30-39 years (73.9%). Fibroids were more frequent in primigravida (76.1%) followed by P1 (15.2%) and ≥P2 (8.7%). Out of 46 patients 43 (93.5%) delivered by CS (69.76%), NVD (25.58%) and instrumental delivery (4.65%) while 3 patients (6.5%) undergo spontaneous abortions. Most common myoma found in this study was intramural (47.8%) followed by submucous (34.8%) and subserosal (17.4%). Out of 43 deliveries most common complications found was atonic PPH (6.97%) and placenta previa (6.97%) followed by degenerations (2.32%), abruptio placentae (2.32%), malpresentations (2.32%). Out of 43 deliveries 6.9% baby born with low birth weight, IUGR (6.9%), IUFD (4.6%), NICU admission (4.65%) and early neonatal death (2.32%). Conclusions: Pregnancies with fibroids are considered as high-risk pregnancy associated with complications during the antepartum, intrapartum, postpartum period. Pregnant women with myoma can be advised for regular ANC along with TAS for early diagnosis and management of complication.